Impact of Rheumatoid Arthritis on Body Image Disturbance - Congcong ZHOU,; Biyu SHEN,; Qian GAO,; Yi SHEN,; Duanying CAI,; Zhifeng GU,; Xujuan XU, (Archives of Rheumatology, 2019)
Objectives: This study aims to explore body image disturbance (BID) in Chinese patients with rheumatoid arthritis (RA). Patients and methods: A total of 211 RA patients (30 males, 181 females; mean age 50.4±12.4 years; range, 20 to 81 years) and 203 age-matched healthy subjects (26 males, 177 females; mean age 49.6±5.6 years; range, 34 to 64 years) were included in this study. Patients were assessed by Body Image Disturbance Questionnaire (BIDQ), Visual Analog Scale, Health Assessment Questionnaire-Disability Index, disease activity score in 28 joints, Short Form 36 health survey, Hospital Anxiety and Depression Scale, Rosenberg Self-Esteem Scale and erythrocyte sedimentation rate. Results: The mean disease duration of RA patients was 7.2±8.2 years. BID occurrence in RA patients was reported in 24.2% of the cases, which was significantly higher than the healthy subjects with 3%. Stepwise logistic regression analysis demonstrated that social function (p<0.05) and anxiety (p<0.01) explained higher BIDQ score. Conclusion: Body image disturbance was common in Chinese RA patients. Rheumatologists and nurses should attach great importance to BID in RA patients, particularly in those with poor social function and anxiety, by examining their physical limitations and psychological disability.